Pengaruh Depresiasi Terhadap Profitabilitas Pada Perusahaan Daerah Air Minum Di Kabupaten Lebak - Dini Arifian; Hayatinufus Siatan; Nia Ulfa Hayatul; Ratu Neneng Rozbiati (E-Journal Studia Manajemen, 2012)
This study was conducted to determine the effect of depreciation on profitability as measured by ROA. Where the object of the research is the Regional Water Company Lebak. Condition of Lebak PDAM is still included in the unfavorable conditions in which the company has not been able to fulfill all obligations of operating expenses. The level of profitability is still very low, One of the factors that influence these conditions is the depreciation expense increased significantly. In this study the authors used the calculation of ROA (Return On Assets) to measure the level of profitability. This was done to see the extent to which the effectiveness of the company's fixed assets existing receipts in generating profits as much as possible. Based on the results of that there is the influence of the depreciation of the profitability ratio on the Regional Water Company (PDAM) Kabuten Lebak, where variable X is calculated based on the proportion of the burden deprasiasi and Y is calculated using the ratio of ROA. that is equal to 69.22% and 30.78% are influenced by other factors.